Decarboxylative Reactions: An Efficient and Versatile Strategy for Organic Transformations - Cai, Xiao-hua; Yang, Mengzhi; Xie, Bing (Current Organic Chemistry, 2018)
Carboxylic acids are one type of the most common, readily available and structural diverse synthetic sources which gradually serve as versatile connection points in organic transformations. The decarboxylative reaction of carboxylic acids has attracted great attention in providing an efficient and powerful strategy for the construction of various valuable molecular skeletons. Over the past decades, a number of obvious and satisfactory achievements in the field have constantly emerged. The review mainly introduces recent advances on the decarboxylative reactions based on aliphatic, alkenylic or carbonic, aromatic and alkynylic acids as decarboxylative partners for the functionalization of C(sp3)-H, C(sp2)-H and C-heteroatom bonds since 2011.
Keywords: coupling reaction